Entrepreneurship, institutional framework and support mechanisms in the EU - Apostolopoulos, Nikolaos (Assistant Professor in Entrepreneurship and Innovation); Chalvatzis, Konstantinos; Liarnkovas, Pan. (Panagiōtēs), 1963- (Emerald Publishing, 2021)
Entrepreneurship, Institutional Framework and Support Mechanisms in the EUsheds light on the important and yet crucially under-explored interactions between entrepreneurship, institutions and support mechanisms within the EU.